A novel mitovirus detected in Diaporthe rudis, a fungus associated with Phomopsis dieback on grapevines - Kocanová, Mária; Eichmeier, Aleš; Botella, Leticia (Archives of virology, 2020)
The genome sequence of a mitovirus found in an isolate of Diaporthe rudis, one of the causal agents of Phomopsis dieback on grapevines, was determined by two high-throughput sequencing approaches, small RNA and total RNA sequencing. The genome of this mitovirus is 2,455 nt in length and includes a single large open reading frame (ORF) encoding an RNA-dependent RNA polymerase (RdRp). A BLASTx comparison of the full-length genome sequence showed the highest similarity (54.15%) with that of Colletotrichum falcatum mitovirus 1 (CfMV1). Our results reveal a new member of the genus Mitovirus first detected in D. rudis (Fr.) Nitschke, with the proposed name "Diaporthe rudis mitovirus 1" (DrMV1).
Keywords: otevřené čtecí rámce; nemoci rostlin; Genome, Viral; Fungal Viruses; Whole Genome Sequencing; RNA-Dependent RNA Polymerase; Viral Proteins; genom virový; Saccharomycetales; Genome Size; délka genomu; mykoviry; Phylogeny; sekvenování celého genomu; Plant Diseases; virové proteiny; exprese genu; Open Reading Frames; Vitis; fylogeneze; Gene Expression; RNA-dependentní RNA-polymerasa